Desempenho do eletrocardiograma no diagnóstico da hipertrofia ventricular esquerda em hipertensos na presença de bloqueio de ramo esquerdo - Burgos, Paula Freitas Martins [UNIFESP] (2017)
Background: Left ventricular hypertrophy (LVH) is an important risk factor for cardiovascular events, and the electrocardiogram (ECG) usually starts its identification. Objective: To evaluate the impact of the left bundle branch block (LBB) in the diagnostic of LVH by ECG in hypertensive patients. Methods: We studied 2,240 hypertensive patients. All patients underwent ECG and echocardiography (ECHO). We evaluated the electrocardiographic criteria most often used for the diagnosis of LVH: Cornell voltage, Cornell product voltage, Sokolow-Lyon voltage, Sokolow-Lyon product, RaVL, RaVL product RaVL + SV3, relationship RV6 / RV5, strain pattern, left atrial enlargement and QT interval and the BRE was identified when: QRS duration ≥120ms; wave absence of "q" in DI, aVL, V5 and V6; R waves and extended with notches and / or slurrying medium in terminal DI, aVL, V5 and V6; wave "r" with slow growth V1 to V3 may occur QS; S extended waves with thickening and / or notches V1 and V2; intrinsecoid deflection in V5 and V6 ≥0,05 s, electrical axis between -30º and + 60º; ST depression and asymmetric T wave as opposed to medium-terminal delay. The LVH identification pattern was the mass indexed of left ventricular (LVMI), obtained by echocardiography in all participants. Results: The ages ranged 58.7 ± 11.3 years, 684 (30.5%) males and 1,556 (69.5%) females. In participants without LBB, the ECG sensitivity to the presence of LVH ranged from 7.6 to 40.9% and specificity from 70.2 to 99.2%. In participants with LBB, sensitivity to LVH ranged from 11.9 to 95.2% and specificity from 6.6 to 96.6%. Among the criteria for LVH with best performance, the highlight was the Sokolow-Lyon voltage to  3,0mV with sensitivity of 22.2% (95%CI 15.8 - 30.8) and specificity of 88.3% (95% CI 77.8 - 94.2). Conclusion: In hypertensive patients with LBB, the most commonly used criteria for detection of LVH on ECG showed significant decrease in sensitivity and specificity performance. In this scenario, the Sokolow-Lyon voltage 3,0mV showed better behavior.